Determinantes de la condición de regularización de los comerciantes informales en los mercados de la ciudad de Riobamba. - Camacho Torres, Roberth Renán (2023)
This research focuses on identifying the determinants that influence the regularitory condition of informal traders in the city of Riobamba. For this purpose, the quantitative approach and hypothetical-deductive type of research were used, formulating hypotheses based on observations and empirical data to later be confirmed or refuted through tests. The process consisted of applying a probabilistic Logit model; 250 surveys were carried out in order to analyze the determinants of regularization. The results revealed that, in both regularized and non-regularized informal traders, there is a greater presence of women. Likewise, differences in age were identified: non-regularized informal traders tend to concentrate in the range of 30 to 40 years, while regularized ones are mostly found in the ranges of 20 to 30 years and 30 to 40 years. To promote formalization, they suggest the implementation of training programs, access to financing and awareness campaigns about the benefits of formalization. The importance of addressing the tax burden and tax compliance is highlighted to facilitate the transition from informality to formality, which would benefit both traders and the economy in general.